Analisis Asas Pemikiran al-Shatibi (w.790H) Berhubung Teori Bid’ah dalam Karyanya al-‘Itisam: An Analysis on the Basic Thought of al-Shatibi (d.790H) Regarding Bid’ah Theory through His Work al-‘Itisam - Syed Jaafar, Syed Mohd Jeffri; Man, Saadan; Pauzi, Norhidayah; Ramli, Mohd Anuar; Hassan, Mohd Rosdi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2018)
Al-Shatibi who was one of the prominent scholars during eight century AH from Granada present us with a comprehensive understanding of bid‘ah with a specific meaning. The definitions presented by him has been a continuing debate in the discussion of Islamic law. Thus, this study aims to examine his view fundamentally on the bid‘ah theory and its implementation in making related fatwa. In order to achieve the intended objectives, this study will be fully implemented by using the library research method based on qualitative evaluation. The study found that al-Shatibi developed the basic theory which had been put forward by Imam Malik who at that time interpreting bid‘ah in one way only, which was all will leading to straying. According to him, bid‘ah is everything which is related with religion either in forms of worshipping act or traditional practice that is not practice by earlier generations. The study also found that al-Shatibi’s views on bid‘ah theory not suitable to be practised in society especially in Malaysia which has been in line with the views of the al-Shafi‘i sect on the issue.